2011
DOI: 10.5402/2011/131087
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling and Simulation of Hydrodynamics in a Fluidized Bed Dryer with Experimental Validation

Abstract: Gas-solid fluidized bed dryers are used in a wide range of industrial applications. With applying computational fluid dynamic (CFD) techniques, hydrodynamics of a two-dimensional nonreactive gas-solid fluidized bed dryer was investigated. A multifluid Eulerian model incorporating the kinetic theory for solid particles was applied to simulate the unsteady state behavior of this dryer and momentum exchange coefficients were calculated by using the Syamlal-O'Brien drag functions. A suitable numerical method that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Syamlal and O'Brien drag function gives a better results compared to other drag models, and it is more suitable for predicting the hydrodynamics of gas-solid flow in fluidized beds [9,11].…”
Section: Drag Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Syamlal and O'Brien drag function gives a better results compared to other drag models, and it is more suitable for predicting the hydrodynamics of gas-solid flow in fluidized beds [9,11].…”
Section: Drag Modelmentioning
confidence: 99%
“…Hamzehei [9] compared the CFD simulation predicted results using the Syamlal and O'Brien drag model to the experimentally measured pressure drop, and found that the model predictions were in good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of researches have been done in order to understand and to determine the best parameters for different fluidized bed application. Mahdi Hamzehei [3] in his study has investigated solid particles diameter and superficial velocity effect on the reactor hydrodynamics using Eulerian-Eulerian model with Syamlal-O'Brian drag function. The pressure drop and bed expansion ratio of the simulation were in good agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The three popular and most widely used drag models are Gidaspow, Wen-Yu and Syamlal and O'Brien model [16,[20][21][22]. Syamlal and O'Brien drag model is found to predict better hydrodynamic results compared to other models, and therefore more suitable for investigating the hydrodynamics of gas-solid bubbling fluidized bed combustors [10,16].…”
Section: O the Euler-euler Approach Equationsmentioning
confidence: 99%